Effects of Kinesio Tape compared with non-elastic sports tape and the untaped ankle during a sudden inversion perturbation in male athletes - Briem, K.; Eythorsdottir, H.; Magnusdottir, R. G.; Palmarsson, R.; Runarsdottir, T.; Sveinsson, T. (Journal of Orthopaedic & Sports Physical Therapy, 2011)
STUDY DESIGN: Controlled laboratory study. OBJECTIVES: To examine the effect of 2 adhesive tape conditions compared to a no tape condition on muscle activity of the fibularis longus during a sudden inversion perturbation in male athletes (soccer, team handball, basketball). BACKGROUND: Ankle sprains are common in sports and the fibularis muscles play a role in providing functional stability of the ankle. Prophylactic ankle taping with non-elastic sports tape has been used to restrict ankle inversion, while kinesio tape is elastic and has not been studied for that purpose. METHODS: Fifty-one male premier-league athletes were tested for functional stability of both ankles with the Star Excursion Balance Test. Based on the results, those with the 15 highest and those with the 15 lowest stability scores were selected for further testing. Muscle activity of the fibularis longus was recorded with surface electromyography during a sudden inversion perturbation. Each participant was tested under 3 conditions; with the ankle taped with non-elastic, white sports tape, kinesio tape, and with no tape. Differences in mean muscle activity were evaluated with a 3-way mixed model ANOVA for the 3 conditions across four 500 ms time-frames (within subject factors) and between the 2 groups of stable versus unstable participants (between subjects factor). Differences in peak muscle activity and in the time to peak muscle activity were evaluated with a 2-way mixed model ANOVA for the 3 conditions (within subjects factor), between the 2 groups (between subjects factor). RESULTS: Significantly greater mean muscle activity was found when ankles were taped with non-elastic tape compared to no tape, while kinesio tape had no significant effect on mean or maximum muscle activity compared to the no tape condition. Neither stability level nor taping condition had a significant effect on the amount of time from perturbation to maximum activity of the fibularis longus muscle. CONCLUSION: Non-elastic sports tape may enhance dynamic muscle support of the ankle. The efficacy of kinesio tape in preventing ankle sprains via the same mechanism is unlikely as it had no effect on muscle activation of the fibularis longus.